Preparation method for synthesizing high-selectivity 2, 5-dimethyl-2, 4-hexadiene through one-step method
By using the one-step synthesis method of zeolite nanocrystalline catalyst using MCM-22/Cu(Ⅰ) zeolite nanocrystalline catalyst, the problems of many reaction steps, low efficiency, low selectivity and easy catalyst accumulation in traditional synthesis methods are solved, and high selectivity is achieved and high efficiency synthesis of 2,5-dimethyl-2,4-hexadiene reduces production costs and environmental impacts.
Patent Information
- Application Number
- CN202411591508.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art synthesis of 2,5-dimethyl-2,4-hexadiene has problems such as low multi-step reaction efficiency, low selectivity, easy catalyst carbon deposits and environmental pollution, and high reaction pressure limits industry. application.
The MCM-22/Cu(Ⅰ) zeolite nanocrystal catalyst is synthesized by one-step method, using the unique pore structure and acidic characteristics of the catalyst to improve the diffusion path and catalytic activity of the reactants and reduce the risk of carbon deposits.
High selectivity and high efficiency 2,5-dimethyl-2,4-hexadiene synthesis is achieved, reducing production costs and environmental impacts, and improving the catalyst's anti-carbon accumulation performance and service life.
Smart Images

Figure CN119462318A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic synthesis, and particularly relates to a one-step method for synthesizing 2,5-dimethyl-2,4-hexadiene with high selectivity. Background Art
[0002] As an important chemical raw material, the research on the synthesis method of 2,5-dimethyl-2,4-hexadiene has always been a hot topic in the chemical industry. Traditional synthesis methods usually involve multi-step reactions, which are not only inefficient but also often accompanied by the production of side reactions, resulting in low product selectivity. In addition, the catalysts used in many traditional methods may be corrosive during the reaction, causing damage to the equipment and causing environmental pollution. Therefore, the development of an efficient and environmentally friendly synthesis method to reduce the number of steps, improve selectivity, reduce energy consumption and environmental impact has become an urgent problem to be solved in this field.
[0003] In this context, the technology of one-step synthesis of 2,5-dimethyl-2,4-hexadiene came into being. The core of this technology is to use specific catalysts, such as niobic acid catalysts (Master's thesis of East China University of Science and Technology), to directly prepare the target product through the dehydration condensation reaction of isobutylene / isobutyraldehyde as raw materials. This method simplifies the process flow, improves the conversion rate of raw materials and the selectivity of products, and is non-corrosive to equipment and has little environmental pollution. However, the catalyst used in this process requires a high reaction pressure of about 5 to 7 MPa, which limits its wide application in industry. In order to solve this problem, researchers are committed to developing catalysts that still have high catalytic activity at lower pressures. Li Linlin et al. (Synthesis of 2,5-dimethyl-2,4-hexadiene from tert-butyl alcohol and isobutylaldehyde catalyzed by citric acid-modified SAPO-11 molecular sieve [J]. Industrial Catalysis, 2014, 22(01): 56-60.) used SAPO-11 molecular sieve as a catalyst and treated it with citric acid to improve its activity. They synthesized 2,5-dimethyl-2,4-hexadiene at low pressure, but there are also some problems. First, under high temperature and high pressure conditions, especially in the presence of water vapor, the structure of SAPO-11 may degrade to form aluminum phosphate, resulting in the loss of active sites. Second, SAPO-11 may accumulate carbonaceous substances during the catalytic reaction. These carbonaceous substances cover the catalyst surface, hindering the contact of reactants and the use of active sites, thereby reducing the activity of the catalyst.
[0004] Another example is a Chinese patent document (application number CN202211141953.0) that discloses a method for synthesizing 2,5-dimethyl-2,4-hexadiene by a Prince condensation reaction based on heteropoly acid catalysis. The method uses isobutylene (IB) / isobutyraldehyde (IBA) as reactants and is prepared by a Prince condensation reaction under the conditions of SiO2-loaded heteropoly acid catalyst. The catalyst prepared by this method is low in price, but it also faces some problems. First, as the SiO2 content increases, the concentration of hydroxyl groups on the surface of the carrier decreases, resulting in a weakening of the interaction between the active metal and the carrier, which reduces the activity of the catalyst. Secondly, the packing density of the SiO2-Al2O3 microsphere catalyst decreases with the increase of the SiO2 content. This is because the Si-O-Al structure formed after the introduction of SiO2 causes the microsphere sample to shrink during aging and calcination. Finally, the SiO2-Al2O3 microsphere catalyst will cause the diffusion of product and reactant molecules to be hindered due to the smaller pore size in the catalytic reaction, resulting in "carbon deposition" and deactivation of the catalyst.
[0005] Therefore, finding a catalyst with high yield and good resistance to carbon deposition is of great significance for improving production efficiency and reducing costs. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a one-step synthesis method for preparing 2,5-dimethyl-2,4-hexadiene with high selectivity. The MCM-22 molecular sieve exhibits good anti-coking performance due to its unique pore structure and acidic properties. There are two independent and mutually incommunicable pore systems in its skeleton structure. Small molecular reactants can pass through the ten-membered ring window to enter the internal sinusoidal pores and super cages, and react inside the molecular sieve; while large organic molecules cannot pass through the ten-membered ring window of the inner pore system, so they cannot react in the ten-membered ring pores. The pore structures of the ten-membered ring and the twelve-membered ring enable the reactants to effectively enter the interior of the catalyst, while reducing the risk of carbon deposition of macromolecular substances. The present invention provides a more efficient diffusion path for reactant and product molecules by synthesizing the MCM-22 / Cu(Ⅰ) zeolite nanocrystal catalyst by a one-step method, which helps to reduce the formation of carbon deposition and improve the catalytic efficiency. This improved diffusion performance, coupled with its larger surface area, makes the MCM-22 / Cu(Ⅰ) zeolite nanocrystals have higher activity and selectivity in catalytic reactions. The nano-scale MCM-22 molecular sieve has a higher specific surface area and more external Acid sites, these characteristics make them show superior performance in catalytic reactions. Due to the size effect of nanocrystals, they are usually superior to micron-level materials in strength and hardness, which provides better protection for their wear resistance. In addition, during the preparation of nanocrystals, due to smaller grain boundaries and size effects, better thermal stability and high temperature resistance can be achieved, which is particularly important for high-temperature catalytic applications.
[0007] Finally, the preparation process of MCM-22 / Cu(Ⅰ) zeolite nanocrystal catalyst is relatively simple, with high solid phase yield and high structural integrity, all of which help to reduce production costs and improve the feasibility of industrial applications. In summary, the one-step synthesis of highly selective 2,5-dimethyl-2,4-hexadiene using MCM-22 / Cu(Ⅰ) zeolite nanocrystal catalyst has shown a broader application prospect for improving production efficiency and reducing costs.
[0008] The technical solution adopted to achieve the purpose of the present invention is:
[0009] A one-step method for synthesizing highly selective 2,5-dimethyl-2,4-hexadiene is characterized by comprising the following steps:
[0010] Step 1: Load the MCM-22 / Cu(Ⅰ) zeolite nanocrystalline catalyst into a fixed bed reactor, heat it to 250-300°C, introduce a raw material gas with a mass ratio of isobutyraldehyde to isobutene of 1:3-4, the reaction pressure is 0.1-0.3 MPa, the carrier gas is nitrogen, and the mass space velocity is 6-10 h -1 , the reaction can be continued for 24 to 72 hours to obtain 2,5-dimethyl-2,4-hexadiene;
[0011] Step 2: Take out the MCM-22 / Cu(Ⅰ) zeolite nanocrystal catalyst after the reaction in step 1, place it in a citric acid solution, keep it at 80°C for 4 hours, and then filter and dry it. This reaction process is repeated 3 times, wherein the mass of the citric acid solution is 10 to 30 times the mass of the MCM-22 / Cu(Ⅰ) zeolite nanocrystal catalyst;
[0012] Step 3: Calcine the MCM-22 / Cu(Ⅰ) zeolite nanocrystal catalyst filtered and dried three times in step 2 at 450-500°C for 4-8 hours to obtain the regenerated MCM-22 / Cu(Ⅰ) zeolite nanocrystal catalyst, which can be used in step 1.
[0013] Furthermore, in step 2, the citric acid solution is a solution with a mass ratio of citric acid to deionized water of 1:4 to 10.
[0014] Furthermore, the mass loss of the MCM-22 / Cu(Ⅰ) zeolite nanocrystalline catalyst after calcination in step three is less than 2% compared with that before the reaction.
[0015] Furthermore, the preparation method of the MCM-22 / Cu(Ⅰ) zeolite nanocrystalline catalyst comprises the following steps:
[0016] S1: After dissolving sodium aluminate and sodium hydroxide in deionized water, add hexamethyleneimine and white carbon black, stir at 800 r / min for 1 h, put the above mixture into a reactor lined with polytetrafluoroethylene, and age at 40-50° C. for 24 h to obtain a mixture 1, wherein the above raw materials are calculated by mass ratio: white carbon black: sodium aluminate: sodium hydroxide: hexamethyleneimine: deionized water = 1: 0.04-0.06: 0.1-0.2: 0.5-1: 4.5-7;
[0017] S2, dissolving sodium hydroxide in ionized water, adding aluminum oxide, stirring until a clear solution is obtained, then slowly dropping hexamethyleneimine, adding white carbon black after the dropping is completed and stirring is uniform, stirring at 400 r / min for 2 hours, then adding copper ammonia complex formed by dissolving cupric chloride in ammonia water, and continuing stirring at 400 r / min for 30 minutes to obtain a mixture 2, wherein the above raw materials are calculated by mass ratio, white carbon black: aluminum oxide: hexamethyleneimine: sodium hydroxide: deionized water: ammonia water: copper chloride = 1: 0.025-0.05: 0.2-0.4: 0.05-0.12: 4.5-5.8: 1-2.8: 0.25-0.7;
[0018] S3: Add mixture 1 to mixture 2, stir at 400 r / min for 30 minutes at room temperature, place in a drying oven at 40° C., dry for 0.5 to 5 hours, and make it lose weight by 10% to 30%, to obtain a solid gel-like mixture 3;
[0019] S4: placing the mixture in an open glass container, placing the glass container in the inner lining of the reactor, adding 5-20 ml of deionized water outside the glass container, crystallizing at 150° C. for 1-3 days under steam-assisted conditions, washing and drying to obtain a crystalline product;
[0020] S5: solid-state grinding the crystalline product and citric acid and calcining at 500-550° C. for 4-8 hours, wherein the mass ratio of the crystalline product to the citric acid is 1:0.2-0.35, thereby obtaining a MCM-22 / Cu(Ⅰ) zeolite nanocrystalline catalyst.
[0021] Furthermore, in S3, the mass of the mixture one is 20% to 300% of the mass of the mixture two.
[0022] The MCM-22 / Cu(Ⅰ) zeolite nanocrystal catalyst showed significant beneficial effects in the preparation of 2,5-dimethyl-2,4-hexadiene. The application of this catalyst not only improved the yield of the reaction, but also significantly enhanced the catalyst's anti-coking performance. MCM-22 zeolite provides efficient catalytic active centers for the reaction due to its unique pore structure and acidic properties. The introduction of Cu(Ⅰ) is achieved by introducing Cu(Ⅱ) into the molecular sieve framework during the synthesis process and then reducing it to Cu(Ⅰ) with citric acid, which further optimizes the performance of these active centers, making the reaction conditions milder and improving the selectivity of the target product. In addition, the design of this catalyst also takes into account its stability and durability in actual industrial applications. By precisely controlling the size and distribution of nanocrystals, the wear and deactivation during long-term operation are reduced, thereby extending the service life of the catalyst.
[0023] In the process of preparing 2,5-dimethyl-2,4-hexadiene, the use of MCM-22 / Cu(Ⅰ) zeolite nanocrystal catalyst also helps to reduce the occurrence of side reactions and reduce the risk of carbon deposition, which is crucial to improving the economy and environmental friendliness of the catalyst. Carbon deposition is a common problem in the catalytic process, which will cover the active sites and cause the catalyst to deactivate. The high anti-carbon deposition performance of MCM-22 / Cu(Ⅰ) zeolite nanocrystal catalyst means that it can maintain high activity for a longer time, reducing the frequency of catalyst replacement and reducing production costs. At the same time, the high selectivity of this catalyst also reduces the generation of by-products and improves the utilization rate of raw materials, which is of great significance to the sustainability of chemical production.
[0024] In summary, the MCM-22 / Cu(Ⅰ) zeolite nanocrystal catalyst not only improves the reaction efficiency but also reduces the production cost and environmental impact in the preparation of 2,5-dimethyl-2,4-hexadiene, demonstrating its great potential in industrial catalytic applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Flow chart of the one-step synthesis of highly selective 2,5-dimethyl-2,4-hexadiene. DETAILED DESCRIPTION
[0026] One-step synthesis of highly selective 2,5-dimethyl-2,4-hexadiene:
[0027] Embodiment 1:
[0028] Step 1: 1 g of MCM-22 / Cu(Ⅰ) zeolite nanocrystal catalyst was loaded into a fixed bed reactor, heated to 250°C, and then introduced a raw gas with a mass ratio of isobutyraldehyde to isobutene of 1:4. The reaction pressure was 0.1 MPa, the carrier gas was nitrogen, and the mass space velocity was 6 h -1 , the reaction can be continued for 30 hours to obtain 2,5-dimethyl-2,4-hexadiene;
[0029] Step 2: Take out the MCM-22 / Cu(Ⅰ) zeolite nanocrystal catalyst after the reaction in step 1, place it in a citric acid solution, wherein the mass ratio of citric acid to deionized water is 1:5, keep it at 80°C for 4 hours, filter and dry it, and repeat this reaction process 3 times, wherein the mass of the citric acid solution is 20mL;
[0030] Step 3: Calcine the MCM-22 / Cu(Ⅰ) zeolite nanocrystal catalyst filtered and dried three times in step 2 at 500°C for 5 hours to obtain the MCM-22 / Cu(Ⅰ) zeolite nanocrystal catalyst, which can be used in step 1.
[0031] The preparation method of the MCM-22 / Cu(Ⅰ) zeolite nanocrystalline catalyst comprises the following steps:
[0032] S1: After dissolving 0.15 g of sodium aluminate and 0.09 g of sodium hydroxide in 10 g of deionized water, 2 g of hexamethyleneimine and 2 g of white carbon black were added, and the mixture was stirred at 800 r / min for 1 h. The mixture was placed in a polytetrafluoroethylene-lined reactor and aged at 50° C. for 24 h to obtain a mixture 1;
[0033] S2, dissolving 0.12 g of sodium hydroxide in 10 g of ionized water, adding 0.05 g of aluminum oxide, stirring until a clear solution is obtained, slowly dropping 0.5 g of hexamethyleneimine, adding 2 g of white carbon black after the dropping is completed and stirring is uniform, stirring at 400 r / min for 2 hours, and then adding a copper-ammonia complex formed by dissolving 0.6 g of copper chloride in 2.6 g of ammonia water, and continuing stirring at 400 r / min for 30 minutes to obtain a mixture II;
[0034] S3: Add mixture 1 to mixture 2, stir at 400 r / min for 30 minutes at room temperature, place it in a drying oven at 40°C and dry it for 0.5 hours to make it lose weight by 12.5%, and obtain a solid gel-like mixture 3.
[0035] S4: Place the mixture three in an open glass container, place the glass container in a 50 mL reactor liner, add 8 ml of deionized water outside the glass container, crystallize at 150° C. for 1 day under steam-assisted conditions, and obtain a crystalline product after washing and drying.
[0036] S5: The crystalline product and citric acid are solid-ground and then calcined at 500° C. for 4 hours, wherein the mass ratio of the crystalline product to the citric acid is 1:0.25, thereby obtaining a MCM-22 / Cu(Ⅰ) zeolite nanocrystalline catalyst.
[0037] Embodiment 2:
[0038] Step 1: 1.5 g of MCM-22 / Cu (Ⅰ) zeolite nanocrystal catalyst was loaded into a fixed bed reactor, heated to 250 ° C, and introduced a raw gas with a mass ratio of isobutyraldehyde to isobutylene of 1:3.5. The reaction pressure was 0.1 MPa, the carrier gas was nitrogen, and the mass space velocity was 6 h -1 , the reaction can be continued for 58 hours to obtain 2,5-dimethyl-2,4-hexadiene;
[0039] Step 2: Take out the MCM-22 / Cu(Ⅰ) zeolite nanocrystal catalyst after the reaction in step 1, place it in a citric acid solution, wherein the mass ratio of citric acid to deionized water is 1:8, keep it at 80°C for 4 hours, filter and dry it, and repeat this reaction process 3 times, wherein the mass of the citric acid solution is 30mL;
[0040] Step 3: Calcine the MCM-22 / Cu(Ⅰ) zeolite nanocrystal catalyst filtered and dried three times in step 2 at 500°C for 5 hours to obtain the MCM-22 / Cu(Ⅰ) zeolite nanocrystal catalyst, which can be used in step 1.
[0041] The method for preparing the MCM-22 / Cu(Ⅰ) zeolite nanocrystalline catalyst comprises the following steps:
[0042] S1: After dissolving 0.05 g of sodium aluminate and 0.12 g of sodium hydroxide in 5.3 g of deionized water, 0.56 g of hexamethyleneimine and 1 g of white carbon black were added, and the mixture was stirred at 800 r / min for 1 h. The mixture was placed in a polytetrafluoroethylene-lined reactor and aged at 50° C. for 24 h to obtain a mixture 1;
[0043] S2, dissolving 0.1 g of sodium hydroxide in 5.4 g of ionized water, adding 0.032 g of aluminum oxide, stirring until a clear solution is obtained, slowly dropping 0.38 g of hexamethyleneimine, adding 1 g of white carbon black after the dropping is completed and the solution is stirred evenly, stirring at 400 r / min for 2 hours, and then adding a copper-ammonia complex formed by dissolving 0.3 g of copper chloride in 1.4 g of ammonia water, and continuing to stir at 400 r / min for 30 minutes to obtain a mixture II;
[0044] S3: Add mixture 1 to mixture 2, stir at 400 r / min for 30 minutes at room temperature, place it in a drying oven at 40°C and dry it for 0.5 hours to make it lose weight by 10.2%, and obtain a solid gel-like mixture 3.
[0045] S4: Place the mixture three in an open glass container, place the glass container in a 50 mL reactor liner, add 8 ml of deionized water outside the glass container, crystallize at 150° C. for 1 day under steam-assisted conditions, and obtain a crystalline product after washing and drying.
[0046] S5: The crystalline product and citric acid are solid-ground and then calcined at 500° C. for 4 hours, wherein the mass ratio of the crystalline product to the citric acid is 1:0.3, thereby obtaining a MCM-22 / Cu(Ⅰ) zeolite nanocrystalline catalyst.
[0047] Embodiment 3:
[0048] Step 1: 2 g of MCM-22 / Cu (Ⅰ) zeolite nanocrystal catalyst was loaded into a fixed bed reactor, heated to 250 ° C, and introduced a raw gas with a mass ratio of isobutyraldehyde to isobutene of 1:4. The reaction pressure was 0.1 MPa, the carrier gas was nitrogen, and the mass space velocity was 10 h -1 , the reaction can be continued for 63 hours to obtain 2,5-dimethyl-2,4-hexadiene;
[0049] Step 2: Take out the MCM-22 / Cu(Ⅰ) zeolite nanocrystal catalyst after the reaction in step 1, place it in a citric acid solution, wherein the mass ratio of citric acid to deionized water is 1:4, keep it at 80°C for 4 hours, filter and dry it, and repeat this reaction process 3 times, wherein the mass of the citric acid solution is 40mL;
[0050] Step 3: Calcine the MCM-22 / Cu(Ⅰ) zeolite nanocrystal catalyst filtered and dried three times in step 2 at 500°C for 5 hours to obtain the MCM-22 / Cu(Ⅰ) zeolite nanocrystal catalyst, which can be used in step 1.
[0051] The specific preparation method of the MCM-22 / Cu(Ⅰ) zeolite nanocrystalline catalyst is the same as that of Example 1
[0052] Comparative Example 1
[0053] 1 g of MCM-22 catalyst was loaded into a fixed bed reactor, heated to 250 °C, and then introduced with a raw gas having a mass ratio of isobutyraldehyde to isobutene of 1:4. The reaction pressure was 0.1 MPa, the carrier gas was nitrogen, and the mass space velocity was 6 h -1 , the reaction was continued for 6 hours to obtain 2,5-dimethyl-2,4-hexadiene;
[0054] The data after the reaction of Example 1 and the comparative example were analyzed, and the results are shown in Table 1:
[0055] Table 1 Comparison of isobutyraldehyde conversion, 2,5-dimethyl-2,4-hexadiene selectivity and yield in Example 1 and Comparative Example 1
[0056]
Claims
1. A one-step method for synthesizing highly selective 2,5-dimethyl-2,4-hexadiene, characterized in that: The following steps are involved: Step 1: Load the MCM-22 / Cu(Ⅰ) zeolite nanocrystalline catalyst into a fixed bed reactor, heat it to 250-300°C, introduce a raw material gas with a mass ratio of isobutyraldehyde to isobutene of 1:3-4, the reaction pressure is 0.1-0.3 MPa, the carrier gas is nitrogen, and the mass space velocity is 6-10 h -1 , the reaction can be continued for 24 to 72 hours to obtain 2,5-dimethyl-2,4-hexadiene; Step 2: Take out the MCM-22 / Cu(Ⅰ) zeolite nanocrystal catalyst after the reaction in step 1, place it in a citric acid solution, keep it at 80°C for 4 hours, and then filter and dry it. This reaction process is repeated 3 times, wherein the mass of the citric acid solution is 10 to 30 times the mass of the MCM-22 / Cu(Ⅰ) zeolite nanocrystal catalyst; Step 3: Calcine the MCM-22 / Cu(Ⅰ) zeolite nanocrystal catalyst filtered and dried three times in step 2 at 450-500°C for 4-8 hours to obtain the regenerated MCM-22 / Cu(Ⅰ) zeolite nanocrystal catalyst, which can be used in step 1.
2. The method for preparing 2,5-dimethyl-2,4-hexadiene by one-step synthesis with high selectivity as claimed in claim 1, characterized in that: The preparation method of the MCM-22 / Cu(Ⅰ) zeolite nanocrystalline catalyst comprises the following steps: S1: After dissolving sodium aluminate and sodium hydroxide in deionized water, add hexamethyleneimine and white carbon black, stir at 800 r / min for 1 h, put the above mixture into a reactor lined with polytetrafluoroethylene, and age at 40-50° C. for 24 h to obtain a mixture 1, wherein the above raw materials are calculated by mass ratio: white carbon black: sodium aluminate: sodium hydroxide: hexamethyleneimine: deionized water = 1: 0.04-0.06: 0.1-0.2: 0.5-1: 4.5-7; S2, dissolving sodium hydroxide in ionized water, adding aluminum oxide, stirring until a clear solution is obtained, then slowly dropping hexamethyleneimine, adding white carbon black after the dropping is completed and stirring is uniform, stirring at 400 r / min for 2 hours, then adding copper ammonia complex formed by dissolving cupric chloride in ammonia water, and continuing stirring at 400 r / min for 30 minutes to obtain a mixture 2, wherein the above raw materials are calculated by mass ratio, white carbon black: aluminum oxide: hexamethyleneimine: sodium hydroxide: deionized water: ammonia water: copper chloride = 1: 0.025-0.05: 0.2-0.4: 0.05-0.12: 4.5-5.8: 1-2.8: 0.25-0.7; S3: Add mixture 1 to mixture 2, stir at 400 r / min for 30 minutes at room temperature, place in a drying oven at 40° C., dry for 0.5 to 5 hours, and make it lose weight by 10% to 30%, to obtain a solid gel-like mixture 3; S4: placing the mixture in an open glass container, placing the glass container in the inner lining of the reactor, adding 5-20 ml of deionized water outside the glass container, crystallizing at 150° C. for 1-3 days under steam-assisted conditions, washing and drying to obtain a crystalline product; S5: solid-state grinding the crystalline product and citric acid and calcining at 500-550° C. for 4-8 hours, wherein the mass ratio of the crystalline product to the citric acid is 1:0.2-0.35, thereby obtaining a MCM-22 / Cu(Ⅰ) zeolite nanocrystalline catalyst.
3. The method for preparing 2,5-dimethyl-2,4-hexadiene by one-step synthesis with high selectivity as claimed in claim 1, characterized in that: In step 2, the citric acid solution is a solution with a mass ratio of citric acid to deionized water of 1:4-10.
4. The method for preparing 2,5-dimethyl-2,4-hexadiene by one-step synthesis with high selectivity as claimed in claim 1, characterized in that: The mass loss of the MCM-22 / Cu(Ⅰ) zeolite nanocrystalline catalyst after calcination in step 3 is less than 2% compared with that before the reaction.
5. The method for preparing 2,5-dimethyl-2,4-hexadiene by one-step synthesis with high selectivity as claimed in claim 2, characterized in that: In S3, the mass of the mixture 1 is 20% to 300% of the mass of the mixture 2.
Citation Information
Patent Citations
Method for synthesizing 2,5-dimethyl-2,4-hexadiene via Prince condensation reaction catalyzed by heteropolyacid
CN115477568B